Nutritional and other causes of hypertension in district Lakki Marwat, NWFP, Pakistan - Khattak, Muhammad Muzaffar Ali Khan; Jan, Akbar (2006)
This study was designed to identify the causes of hypertension in District Lakki Marwat, North West Frontier Province (NWFP)-Pakistan. Eight hundred individuals in the age range of 21 - 60 years (81 % male and 19 % female) from the urban & rural areas were randomly selected. A voters list was obtained from the Assistant Election Commissioner’s Office and every 7th person was randomly selected as a study case in each of the selected areas. The height, weight, blood pressure, socio- economic, demographic and nutritional information was recorded on questionnaire. The data was compiled and assessed for nutritional status, hypertension and other factors for any possible association. None of the respondents was in the category of optimal blood pressure. In the categories of optimal blood pressure, normal blood pressure, high normal blood pressure, hypertension stage 1, hypertension stage 2 and hypertension stage 3 on overall basis the percentages were 0.00, 71.75, 14.65, 4.87, 3.87 & 4.62 respectively, for the urban area the percentages were 0.00, 70.84, 12.85, 7.52, 4.07 & 4.70 respectively and for the rural area the percentages were 0.00, 72.34, 15.80, 3.11, 3.95 & 4.78 respectively. The association of the hypertension was significant with the different variables i.e. basal metabolic index (BMI), socioeconomic status (job and family responsibilities, social problems & enmity), nutritional habit (particularly excessive saturated fat & salt intake), smoking and lack of knowledge about the hypertension. This study suggests that the causes of hypertension are due to poor dietary habits, social and economic problems in the District Lakki Marwat, North West Frontier Province (NWFP)-Pakistan